Non-genetic factors affecting the meat quality and flavor of Inner Mongolian lambs: A review - Liu, Yuning; Li, Runhang; Ying, Ying; Zhang, Yandong; Huang, Yiying; Wu, Hongxin; Lin, Kejian (Frontiers in Veterinary Science, 2022)
The Inner Mongolia Autonomous Region ranks first among the five major pastoral areas in terms of lamb breeding of China. The Inner Mongolia Autonomous Region has a vast territory, with many famous grasslands and thousands of forage plants and multiple local high-quality lamb breeds. Therefore, understanding the relationship among Inner Mongolian lamb, meat quality, and flavor will improve the production of high-quality mutton. The regulation of meat quality and flavor will have a profound impact on the deep processing and income-generating capabilities of mutton. Nongenetic factors affect the quality and flavor of mutton, which are more intuitive than genetic factors. In this review, we cover the contributions made by scientists to explore and improve the quality and flavor of Inner Mongolia lambs through non-genetic means, compare the differences between grazing and house-feeding in detail, and summarize some feed additives.